2023 Report : "An Analysis of the Demographic and Socio-Economic Characteristics of Quebec's English-Speaking Community Compared to the French-Speaking Population" with a Focus on the RTS de la Montérégie-Oues - Montérégie West Community Network (MWCN) (2023)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Health Passport : When Language Matters / Passport santé : Question de langue - Assistance and Referral Centre (ARC) (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

Project Report : Community Health and Social Services Network (CHSSN) : Community Radio : January 1 to March 31, 2007 - Howarth, Kelly; Kueber, Russell (Community Health and Social Services Network (CHSSN), 2007)
The findings and processes were to be documented and shared with the Lower North Shore (local radio station and regional English-speaking organization, COASTERs Association). In addition, consultation and support was to be given to both service providers to increase their capacity to better serve the English-speaking regions in the future.

Building a New Bridge of understanding and discovery of the English-speaking Community of the Monteregie Centre (South Shore) - Richardson, Mary (Assistance and Referral Centre)